2007
DOI: 10.1038/sj.npp.1301509
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT2C Receptor Agonist Ro60-0175 Reduces Cocaine Self-Administration and Reinstatement Induced by the Stressor Yohimbine, and Contextual Cues

Abstract: Previously, we showed that the 5-HT 2C receptor agonist Ro60-0175 reduces cocaine self-administration, and the ability of cocaine to reinstate responding after extinction of drug-seeking behavior. The present experiments extended these findings further by determining whether the effects of Ro60-0175 on self-administration were sustained with repeated treatment, and whether Ro60-0175 altered reinstatement induced by the pharmacological stressor yohimbine, or by the context in which self-administration occurred.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 64 publications
5
98
0
Order By: Relevance
“…cocaine-seeking behaviors (Neisewander and Acosta, 2007;Fletcher et al, 2008). Therefore, it is significant that the effect of SCH23390 in the OFC could be overcome by co-administration of the D1-like receptor agonist, SKF81297 (Figure 2e left), at a dose that alone failed to reinstate cocaine-seeking behavior in rats that could exhibit reinstatement in response to cocaine priming (Figure 2e right).…”
Section: Discussionmentioning
confidence: 99%
“…cocaine-seeking behaviors (Neisewander and Acosta, 2007;Fletcher et al, 2008). Therefore, it is significant that the effect of SCH23390 in the OFC could be overcome by co-administration of the D1-like receptor agonist, SKF81297 (Figure 2e left), at a dose that alone failed to reinstate cocaine-seeking behavior in rats that could exhibit reinstatement in response to cocaine priming (Figure 2e right).…”
Section: Discussionmentioning
confidence: 99%
“…; Figure 9]. There was a main effect of treatment on latency to the first lever press during the reinstatement session versus VEH-COC [F (3,18) = 4.27; p < 0.05; data not shown]; a priori comparisons revealed that 1.5 mg/kg WAY163909 significantly increased latency to the first lever press versus VEH-COC (p < 0.05; data not shown). Neither 0.5 nor 1 mg/ kg of WAY163909 altered the latency to the first lever press versus VEH-COC (p < 0.05; data not shown).…”
mentioning
confidence: 96%
“…Systemic injections of Ro 60-0175 (an agonist of 5-HT 2C serotonin receptors) or SR141716A (an antagonist of cannabinoid receptor 1, CB1) decrease drug priming-and discrete cue-induced reinstatement of drug seeking (Grottick et al 2000;De Vries et al 2001, 2003Burbassi & Cervo 2008). Based on these studies, Fletcher et al (2008) examined the effect of systemic injections of Ro 60-0175 on context-induced reinstatement of cocaine seeking, and Diergaarde et al (in press) examined the effect of systemic injections of SR141716A on context-induced reinstatement of nicotine seeking. They found that these injections decrease context-induced reinstatement.…”
Section: Pharmacology and Neuroanatomy Of Context-induced Reinstatementmentioning
confidence: 99%
“…During the reinstatement tests under extinction conditions, responding on the previously active lever leads to contingent presentations of the discrete drug cue but not the drug. Using variations of this procedure, we and others found context-induced reinstatement of heroin (Bossert et al , 2006(Bossert et al , 2007, cocaine (Crombag et al 2002a;Fuchs et al 2005Fuchs et al -2007Kearns & Weiss 2007;Fletcher et al 2008;Hamlin et al 2008), speedball (Crombag & Shaham 2002), alcohol Zironi et al 2006;Hamlin et al 2007;Marinelli et al 2007;Chaudhri et al 2008) and nicotine (Diergaarde et al in press) seeking (figure 1). In these studies, the magnitude of lever (or nose-poke) responding during tests for contextinduced reinstatement after extinction was similar to that observed on the first extinction session.…”
Section: Introductionmentioning
confidence: 99%